Irrigação e fertilizações orgânica e mineral na cultura do girassol no litoral cearense - Gomes, Krishna Ribeiro (2014)
The arid and semiarid areas of Brazilian northeast are characterized by pronounced temporal and spatial variability of rainfall, contributing to the high risk of dryland and obtaining low yields of harvested crop agriculture. An alternative to mitigate the irregularity of rainfall and soil moisture stress in this region is irrigation, which is a practice that allows the reduction of risks and enables cultures externalize their potential productivity. Knowing the quantity of irrigation water for the development of a culture is crucial to the success of a crop factor as well as the application of alternative sources of fertilizer. The study aimed to evaluate the growth, gas exchange and productivity of sunflower variety Embrapa 122 under different irrigation and organic and mineral fertilization. The study was conducted in full sun in pots and was used a completely randomized factorial 5 x 3 corresponding to five irrigation design (L1=50%, L2=75%, L3=100%, L4=125% e L5=150% of ECA) and three fertilizations (F1=organic source, using bovine biofertilizer aerobic fermentation, F2=mineral fertilizer, based NPK and F3= witness, without fertilizer, with 5 repetitions. When the plants were in full development, gas exchange (photosynthesis, stomatal conductance, transpiration, and internal CO2 concentration) and growth (plant height, stem diameter and number of leaves) were measured. When the plants reached the maximum development of their productivity, they were harvested and dry biomass of certain leaf, stem and root, the head diameter, 1000 seed weight, dry matter of the chapter, dry matter and seed productivity were measured. The use of different irrigation causes significant effect on all growth parameters and biomass accumulation, gas exchange and productivity, except the number of leaves (NL) and internal temperature of leaves (Ti), and so the lower the effect the smaller the depth applied. Apply biofertilizer plants provides similar increments provided by the application of mineral fertilizers on growth parameters and biomass production increments, and the production and productivity of sunflower, but the photosynthetic parameters is presented as a reducer. There is interaction between irrigation water applied and fertilizers applied in almost all parameters, being the largest irrigation depth x bovine fertilizer and mineral fertilizer that provided the best values.